Penciptaan Peran Tokoh Xiau Mei dalam Naskah Senja dan Penantian Karya Hernandes Saranela Terinspirasi dari Film The Chinese Widow - Shinta Kusuma; Hirwan Kuardhani; Rukman Rosadi (Dance and Theatre Review, 2020)
The Creation of the Character of Xiao Mei in the Play Script of Senja dan Penantian by Hernandes Saranela Inspired by The Chinese Widow Film. The script of Senja dan Penantian written by Hernandes Saranela, tells about the waiting of a Chinese descent girl waiting for her lover to return from the battlefield. This realism script of the play presents its challenges and requires a lot of references. The Chinese Widow film is a source of ideas. Ying's character as the main character is lovely because the play's depth brings out firm acting details. The actress made a series of observations and used the presentation approach to creating the Xiao Mei's character. The creation of this work aims to describe how the actress can portray the character's inner act by using Stanislavski's acting method. In her acting, the actress attains awareness of playing her roles to make the weakness of Xiao Mei's character's strength and uniqueness.Keywords: actor; acting; film